Polypodiaceae endémicas del Perú - León, Blanca (2006)
This family is recognized in Peru with eight genera and more than 110 species (Tryon & Stolze, 1993; Smith et al., 2005; Kessler & Smith, 2005). It is found in a wide range of environments; however, those five endemic species in three genera occur mainly in the Humid Montane and Premontane Forests regions, between 700 and 2500 m elevation. Two species are found in a protected area. Their members occur in a vast range of altitudes, usually associated with forests. Six endemic taxa in one genus are recognized. These taxa are known between 800 and 3650 m elevation, where they generally grow as epiphytes. Only one taxon is found in a protected area.